Facilitating of fourth grade students problem solving skills on gravity. Issue 3 (February 2019) - Gumala, Y; Suhandi, A; Syaodih, E; Maftuh, B; Hermita, N; Samsudin, A
Abstract: This research determinations to designate students' Problem-solving skills on gravity toward elementary level through experiential learning. The indicators of problem-solving skills applied in this research were the indicators definite to the problem-solving skills on impulses and attractions. A descriptive-qualitative design has already been fulfilled to collect data from fourth-grade elementary students' in one of school in Bandung Barat Regency (41 participants: 9-10 years old). The instrument which is developed formed essay with the interview process. The result shows that every characteristic of problem-solving skills has been developed and described such as identification, arguments hypothesis, analysis synthesis and alternate solution. To summarize, the experiential learning is able to designate the 4 th -grade elementary students' problem-solving skills on force and changing.